Processing and properties of Ag/BSCCO PIT tapes containing different proportions of silver metal powder - Santos, Dayse Iara dos [UNESP]; Rodrigues, D.; Rubo, EAA; Cursino, E. (Elsevier B.V., 2004)
Monofilamentary tapes (150 pm thickness) were prepared by swaging and rolling silver tubes containing the Bi:2212 ceramic (granulation below 20 mum) and the silver powder (about 0.8 mum). The study has been made, among other samples, on tapes with nominal proportions of 0, 10 and 20 wt.% of silver. The samples were characterized by SEM, and by electrical measurements under varying applied magnetic field. The measurements of J(c) showed that the addition of 10 wt.% silver powder is very beneficent to this property, doubling the obtained values at 60 K, while the 20 wt.% tape presented very low J(c). The tape with no silver content showed to have a J(c) as high as 2.2 x 10(5) A/cm(2), at 4.2 K, zero applied magnetic field. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: PIT tapes; Ag/BSCCO tapes; Ag/BSCCO composites